Tailoring the dielectric properties of KDP crystals by shock waves for microelectronic and optoelectronic applications. (8th May 2019) - Sivakumar, A; Manivannan, M; Sahaya Jude Dhas, S; Kalyana Sundar, J; Jose, M; Dhas, S A Martin Britto
Abstract: In the present research article, authors report on tailoring the dielectric properties of potassium dihydrogen phosphate (KDP) crystals using supersonic shock waves that is proposed and demonstrated. The present experimentation involves an investigation of loading single pulse of shock waves with different Mach numbers such as 1.7, 1.9, 2.2, 2.4 and 2.5 on KDP crystals using shock tube. The crystalline nature and dielectric behavior of pre and post shock loaded KDP crystals are evaluated by PXRD and impedance analyzer techniques, respectively. Interestingly, shock wave loaded test materials show low dielectric constant compared to pre shock test crystal. Moreover, Mach 1.9 shock wave loaded test crystal shows the lowest dielectric constant compared to other Mach numbers and it is due to the reduction of lattice polarization and domain orientation changes. The experimental results clearly show that the test crystal can be a potential material for microelectronic and optoelectronic applications because it acquires low dielectric constant on shock exposure.